Perawatan Ibu Postpartum dengan Pemanfaatan Tumbuhan Herbal Sesuai Kebiasaan Masyarakat di Kota Lhokseumawe - Yusri Yusri; Mariyati Mariyati; Liza wahyuni (Universitas Pahlawan Tuanku Tambusai, 2026)
The utilization of herbal plants in postpartum care is rooted in familial and hereditary traditions and is believed to expedite the recovery process. Local customs support the use of these herbal plants as a cost-effective, readily accessible, and culturally familiar alternative for postpartum care, aimed at enhancing women's health. This study aims to investigate the utilization of herbal plants during the postpartum period. Employing a qualitative methodology, the study was conducted in the city of Lhokseumawe, utilizing a phenomenological approach. Data collection was executed through in-depth interview techniques, and data analysis was performed using content analysis. Respondents were selected using snowball sampling techniques. The primary data processing and analysis revealed six key themes, namely: purposes for utilizing herbal plants, varieties of plants utilized, sources of processing, benefits, adverse effects, and providers of the medicinal herbs treatment. The use of herbal plants during the postpartum period can provide great benefits if managed wisely and correctly. Recommendations for health professionals include providing counseling on the use of herbal plants.